Faktor-faktor Penyebab Kredit Macet Pada Bank Beserta Cara Penanganannya - Zainab ,; Ferina Oktavia Fadila; Enza Resdiana; Nur Samsi (PUBLIC CORNER, 2023)
This study aims to determine the factors that cause bad credit at Bank Lantabur Syariah Gresik and how to deal with the causes of bad credit.by using qualitative research methods. the process of collecting data in this study was carried out in the first way, namely interviewing employees and customers of Bank Lantabur Syariah Gresik. the next is observation and the last is documentation.Data analysis techniques in this study are data presentation, data analysis and conclusion drawing. The results of this study are the factors that cause bad credit, namely the economic condition of the borrower. for the payment of bad credit by the customer, the bank provides relief by re-contracting based on current capabilities.Keywords: Bad Credit and Banks